Decrease in Factor VII Coagulant Activity during Percutaneous Transluminal Coronary Angioplasty by Heparin-Mediated Lipolytic Action - Mukherjee, Manjari; Scully, Michael F; Kakkar, Vijay V; Philippou, Helen; Lane, David A; Jewitt, David (Thrombosis and Haemostasis, 1997)
Levels of factor VII coagulant activity (FVII: C) and two-chain factor Vila antigen (FVIIa: Ag) were measured in ten patients before and up to 6 h after receiving a bolus of heparin during percutaneous transluminal coronary angioplasty (PTCA). A significant and sustained post-heparin fall in the level of FVII: C was observed (approximately 30%) without any change in the level of FVIIa: Ag. The level of tissue factor antigen within the circulation remained unchanged. The observed decrease in FVII: C coincided with a significant decrease in triglyceride levels presumably due to lipoprotein and hepatic lipase released by the heparin. These findings appear to demonstrate a lipid (triglyceride) dependence of FVII: C. Thus, heparin may act indirectly as antithrombotic agent by limiting a lipid-dependent activation of the extrinsic pathway of coagulation.